Subjective evaluation of health behaviour of patients with chronic kidney disease - Krzyżanowska, Ewa; Polska, Magda; Łuczyk, Robert Jan; Wawryniuk, Agnieszka; Sawicka, Katarzyna; Olszak, Cecylia; Daniluk, Jadwiga (Journal of Education, Health and Sport, 2017)
Abstract The aim of the study: The aim of the study was to evaluate of health behaviour in each of several of patients with chronic kidney disease. Material and methods: In total 116 people diagnosed with chronic kidney disease were tested. The study was conducted from February to April of 2017 in the Nephrology Department of the Regional Clinical Hospital in Zielona Góra, Poland, the Nephrology and Arterial Hypertension Department of the Regional Specialist Hospital in Lublin, Poland as well as in the Private Healthcare Centre “Diaverum” in Lublin, Poland. In the study the Inventory of the Health Behaviour (Inwentarz Zachowań Zdrowotnych, IZZ) was used. IZZ consists of four health behaviour categories: positive mental attitude, preventative actions, healthy eating habits and health practices. The patients who were research subjects determined the frequency of particular factors within the above mentioned categories. The total numerical values determine the overall health behaviour index, whose value lies between 24 and 120 points. The higher the score, the higher the declared frequency of health behaviour. Results: Patients with chronic kidney disease described their health behaviour as average. The highest rated categories were health practices and preventative actions as opposed to healthy eating habits which were rated the lowest. The educational background and place of residence do not influence the health behaviour significantly. The inhabitants of the Lubelskie region (with the capital city of Lublin) rated their health behaviour higher than the inhabitants of the Lubuskie region (with the capital city of Zielona Góra) in all the categories. However, this discrepancy turned out to be statistically insignificant. The age of the patients had a significant impact on the responses of the research subjects. The patients between 60 and 69 had the highest index value, and these under 49 the lowest. Conclusions: The study concludes that women rated their health behaviour higher than men, within the analysed categories except for healthy eating habits, which men rated higher than women. The place of residence did not influence the ratings of the research subjects. People living in urban areas as well as in rural areas rated their health behaviour on a similar level. In the researched group the age is the factor determining the health behaviour – the oldest patients rated their health behaviour the highest. The kind of treatment influences the health behaviour ratings. Patients who are treated with haemodialysis rated their health behaviour higher than those undergoing conservative treatment. Keywords: Health behaviour, chronic kidney disease